Development of UV photodetector structures on silicon - Muhammad Osman (2014)
AlxGa1-xN based UV photodetectors on Si samples grown by RF-MBE technique were characterized to study the effects of varying Al % composition on the optical and structural properties of the samples. Photoluminescence (PL), X-Ray Diffraction (XRD), Microscope and Scanning Electron Microscope (SEM) were used to characterize the samples. In addition to that, I – V and Hall Measurement were also done to study the electrical properties of these samples.